Abandoned babies: where does the responsibility lie? / Ahmad Hazwan Mustafa, Juhfaidzal Azwad Juhari and Mohd Fathanah Shukri Saghiri - Mustafa, Ahmad Hazwan; Juhari, Juhfaidzal Azwad; Shukri Saghiri, Mohd Fathanah (Faculty of Law, 2008)
This research project has been conducted by Ahmad Hazwan bin Mustafa, Juhfaidzal Azwad Juhari and Mohd Fathanah bin Shukri Saghiri and has been supervised by Puan Sivameenambigai d/o Veeriah. This research is pertaining abandonment of children which is currently a universal problem and appears to be taking alarming proportion. The growing concern seems to stem from a realization that despite the legal framework, babies are being abandoned, harmed and sometimes dying as a result. In addition, the research project will be focused on where the responsibility lies in providing care for the children? Does the responsibility lie in the hands of welfare houses or in the hands of parents or only mothers in cases involving illegitimate children? Analysis will also be made to see whether the new-born are sufficiently protected by the existing law provided in Malaysia. Hence, the objective of this study aims to analyze whether Malaysia Law has sufficient punishment for the offenders who commit baby abandonment in both married and unmarried couple scenarios. It also aims to determine the legal perspective from Islamic point of view regarding this issue. In addition, this research will examine whether the Child Act 2001 provides adequate provisions to curb the issue of child abandonment including punishment and responsibility aspects. In analyzing so, Islamic perspective will also be looked into to analyze possible solutions. This research will also look into the Guardianship of Infants Act 1961 as legal authority with regard this issue. The law in United Kingdom and United States will be looked into briefly to understand their legal position pertaining to baby abandonment and interesting developments in the respective countries.